1.2(x+4)=3.6(x-14)

来源:学生作业帮助网 编辑:作业帮作业网 时间:2022/05/21 08:13:29
(x+x)+(x-x)+(x/x)=11.2

(x+x)+(x-x)+(x/x)=11.2(x+x)+(x-x)+(x/x)=11.2(x+x)+(x-x)+(x/x)=11.2(x+x)+(x-x)+(x/x)=11.22x+0+1=11.22

一元二次方程解答!x(5x+4)=5x+44x^2-45=31x-3x^2+22x-24=0(x+8)(x+1)= -12(3x+2)(x+3)=x+14

一元二次方程解答!x(5x+4)=5x+44x^2-45=31x-3x^2+22x-24=0(x+8)(x+1)=-12(3x+2)(x+3)=x+14一元二次方程解答!x(5x+4)=5x+44x^

1、1/2x=2/x+32、x/x+1=(2x/3x+3)+13、2/x-1=4/x²-14、5/x²+x-1/x²-x=0

1、1/2x=2/x+32、x/x+1=(2x/3x+3)+13、2/x-1=4/x²-14、5/x²+x-1/x²-x=01、1/2x=2/x+32、x/x+1=(2x

x/(x-2)-x+14/(x²-4)=2x/(x+2)-1(一定要排列整齐)

x/(x-2)-x+14/(x²-4)=2x/(x+2)-1(一定要排列整齐)x/(x-2)-x+14/(x²-4)=2x/(x+2)-1(一定要排列整齐)x/(x-2)-x+14

4(x+24(x+8)+10x(x+8)=14x(x+24)

4(x+24(x+8)+10x(x+8)=14x(x+24)4(x+24(x+8)+10x(x+8)=14x(x+24)4(x+24(x+8)+10x(x+8)=14x(x+24)4x+24(x+8)

X+X+2+X+4-(X+4)=26

X+X+2+X+4-(X+4)=26X+X+2+X+4-(X+4)=26X+X+2+X+4-(X+4)=26X+X+2+X+4-(X+4)=262X+2=26X=12

(16x^4+4x^2+x)/x=?

(16x^4+4x^2+x)/x=?(16x^4+4x^2+x)/x=?(16x^4+4x^2+x)/x=?(16x^4+4x^2+x)/x=16x^4/x+4x^2/x+x/x=16x^3+4x+1

已知x-x/4=6.求代数式x平方-14x+4/2x平方-20x除(1-x-2-x/12)的值

已知x-x/4=6.求代数式x平方-14x+4/2x平方-20x除(1-x-2-x/12)的值已知x-x/4=6.求代数式x平方-14x+4/2x平方-20x除(1-x-2-x/12)的值已知x-x/

已知x-4/x=6,求代数式2x²-20x/x²-14x+4除(1-x-12/2-x)的值

已知x-4/x=6,求代数式2x²-20x/x²-14x+4除(1-x-12/2-x)的值已知x-4/x=6,求代数式2x²-20x/x²-14x+4除(1-x

解方程:(x-8)/(x-3)-(x-9)/(x-4)=(x+7)/(x+8)-(x+2)/(x+3)

解方程:(x-8)/(x-3)-(x-9)/(x-4)=(x+7)/(x+8)-(x+2)/(x+3)解方程:(x-8)/(x-3)-(x-9)/(x-4)=(x+7)/(x+8)-(x+2)/(x+

4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71

4.2-0.6x=3.6x5x+2x=33.67x-4x=0.752x+7x+2.1=1256x-32x-119=361x+5=2x3x+9=6x4x-28=2x2x+18=7x5x=25*4-15x

3/x-1=4/x 6/x+1=x+5/x(x+1)

3/x-1=4/x6/x+1=x+5/x(x+1)3/x-1=4/x6/x+1=x+5/x(x+1)3/x-1=4/x6/x+1=x+5/x(x+1)3/x-1=4/x1/x=-1x=-16/(x+1

x^4表示( ) A.4x B.x+x+x+x c.x*x*x*x D.x+4

x^4表示()A.4xB.x+x+x+xc.x*x*x*xD.x+4x^4表示()A.4xB.x+x+x+xc.x*x*x*xD.x+4x^4表示()A.4xB.x+x+x+xc.x*x*x*xD.x

0.3+0.3x=0.39 x= 2x-1.5x=7.6x x= 0.36x÷0.3=1.2 x=6(x+1.2)=18.6 x= 7x+2x = 8.1 x= (x-5)÷3=1.7 x=5(x+1.1)=15.5 x= 9x+25=70 x= 7x-4x=2.1 x=

0.3+0.3x=0.39x=2x-1.5x=7.6xx=0.36x÷0.3=1.2x=6(x+1.2)=18.6x=7x+2x=8.1x=(x-5)÷3=1.7x=5(x+1.1)=15.5x=9x

解下列方程: 1.2(x+3)=5x 2.4x+3(2x-3)=(x+4) 3.6(1/2x-4解下列方程:1.2(x+3)=5x 2.4x+3(2x-3)=(x+4)3.6(1/2x-4)+2x=7-(1/3x-1)4.2-3(x+1)=1-2(1+0.5x)

解下列方程:1.2(x+3)=5x2.4x+3(2x-3)=(x+4)3.6(1/2x-4解下列方程:1.2(x+3)=5x2.4x+3(2x-3)=(x+4)3.6(1/2x-4)+2x=7-(1/

先化简再求值先化简再求值:(x-x/x+1)(x+1/x^2+4x+4)(x^2-4/x^2-2x),其中x=-0.5

先化简再求值先化简再求值:(x-x/x+1)(x+1/x^2+4x+4)(x^2-4/x^2-2x),其中x=-0.5先化简再求值先化简再求值:(x-x/x+1)(x+1/x^2+4x+4)(x^2-

(X-3分之x-1-x分之x-4)除以x的平方+3x分之(x+3)(x-2),其中(x-1)(x-2)=0

(X-3分之x-1-x分之x-4)除以x的平方+3x分之(x+3)(x-2),其中(x-1)(x-2)=0(X-3分之x-1-x分之x-4)除以x的平方+3x分之(x+3)(x-2),其中(x-1)(

(2x•x+x•x+2x•x)•2+x•x•6+2x•x•4=600

(2x•x+x•x+2x•x)•2+x•x•6+2x•x•4=600(2x•x+x̶